Impact of a course in evidence-informed policy-making on the acquisition of methodological knowledge: Findings from before-and-after studies conducted on three consecutive cohorts of master students. Issue 3 (October 2019) - Lapointe, Luc
The practice of evidence-informed policy-making (EIPM) consists of systematically searching, analyzing, synthesizing and disseminating the best available research evidence to inform decision-makers about policy problems, policy tools, implementation options, and/or policy evaluation results. Identifying the best available scientific evidence is not a simple task. The vast majority of research evidence contains risks of bias that hinder the reliability of their conclusions. In order to select the soundest available research evidence, policy analysts need to know how to critically appraise research evidence and identify different risks of bias. Formal theories on expertise acquisition in public bureaucracies suggest that these skills and knowledge should be acquired within academia rather than within governmental agencies. We thus created a 45-hour course in EIPM, POL-7061, that was first offered in 2012 to students enrolled in the Master's Program in Public Affairs at Université Laval (Québec, Canada). The course mainly teaches techniques for searching and appraising different types of empirical studies. In 2013, we conducted a before-and-after study to assess the impact of the course on the methodological knowledge of the students. We repeated the exercise on two consecutive cohorts in 2014 and 2015. Mean percent of pre-post improvement on the knowledge test was 37% for the 2013 cohort, 51% for the 2014 cohort and 31% for the cohort of 2015. Teaching techniques in EIPM to Master's students in public affairs is thus feasible and can have a positive impact on their basic methodological knowledge.